Iranian Dietitians' Viewpoints on Virtual Nutritional Consultation on the Instagram Platform: A Descriptive, Cross-sectional Study - Mojtaba Khadem Al-Hoseini; Mostafa Lofti; Farzaneh Mohammadi; Gordon A Ferns; Marzieh Akbarzadeh (Shiraz University of Medical Sciences, 2024)
Background: Today, the use of social media for health care advice has become more popular. The present study aimed to evaluate the opinions of Iranian dietitians on virtual nutritional counseling on the Instagram platform.Methods: The present descriptive, cross-sectional study enrolled Iranian dietitians working in the field of nutrition counseling using Instagram. The link to an online questionnaire including questions on their activity in virtual counseling on Instagram and the challenges of virtual counseling was sent to the 131 participants. Descriptive statistics were used to analyze and interpret the data.Results: Out of 163 dietitians, 131 participated in the study. 47.3% started virtual counseling during COVID-19, and 35.2% had more virtual clients. 58.8% preferred face-to-face counseling for concept transfer, and 43.5% found it more effective. Text and voice messaging were the most practical methods for virtual counseling, with weight loss being the most common topic.Conclusion: During the COVID-19 pandemic, virtual nutritional counseling became more widespread. However, it is believed that face-to-face counseling is more effective in conveying concepts. For virtual platforms, text messaging is the most practical method for nutrition counseling, followed by voice messaging. It has been observed that the elderly have been the least likely people to seek virtual nutrition counseling, while weight loss counseling has been the most frequently requested topic.